2018
DOI: 10.1177/0954409718797734
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal vibration of a resilient wheel under the adhesion limit

Abstract: In order to study the longitudinal vibration law of a resilient wheel under the adhesion limit of different working conditions, two longitudinal vibration models of the resilient wheel of a motor vehicle are established, and the vibration laws and influencing factors of the resilient wheel under different operating conditions are studied by simulation. The model of the resilient wheel under low-speed driving and low adhesive operating conditions is established based on the Fastsim wheel/rail contact theory, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Based on this model they concluded that vehicle dynamics behaviour was much more sensitive to the radical and axial stiffness of the rubber than to its rotational stiffness. Later, Yang et al (2019) established a 6-DOF multi-body model of resilient wheel and integrated it into a metro vehicle dynamics system, to study the longitudinal vibration law of a resilient wheel under the adhesion limit of different working conditions. Material properties for the resilient wheel model were properly selected by making the calculated stiffness close to that measured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this model they concluded that vehicle dynamics behaviour was much more sensitive to the radical and axial stiffness of the rubber than to its rotational stiffness. Later, Yang et al (2019) established a 6-DOF multi-body model of resilient wheel and integrated it into a metro vehicle dynamics system, to study the longitudinal vibration law of a resilient wheel under the adhesion limit of different working conditions. Material properties for the resilient wheel model were properly selected by making the calculated stiffness close to that measured.…”
Section: Introductionmentioning
confidence: 99%
“…While, the validation of the prediction model of the whole vehicle system with the resilient wheel was not given, either the measured rail irregularity was not considered in the working conditions. (Yang et al, 2019)…”
Section: Introductionmentioning
confidence: 99%
“…Claus et al [21,22] established the vertical dynamics model of the ICE railway car to study the possibility of resilient wheels reducing the low frequency interior noise. Yang et al [23] studied the longitudinal vibration law of a resilient wheel under low-and highspeed driving conditions. In previous research, there were hardly any studies on the reduction of vibration and noise for the application of resilient wheels under the operating conditions of the metro.…”
Section: Introductionmentioning
confidence: 99%